2015
DOI: 10.1080/02134748.2015.1065085
|View full text |Cite
|
Sign up to set email alerts
|

Political extremism, group membership and personality traits: who accepts violence? / Extremismo político, pertenencia al grupo y rasgos de personalidad: ¿Quién acepta la violencia?

Abstract: Identity fusion theory proposed that fused individuals have a visceral feeling of oneness with the group and this leads them to engage in radical, violent pro-group behaviours. Other approaches to group extremism link acceptance of violence to right-wing authoritarianism (RWA) and social dominance orientation (SDO). We extended previous research on fusion in three ways. First, by exploring if identity fusion is a significant predictor of the willingness to fight for a group, when controlling for group identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
0
22
0
5
Order By: Relevance
“…These results are consistent with a three-component model of gender nonconformity prejudice (Nagoshi et al 2008), which stresses social conventionalism as the key factor of prejudice toward gender nonconformists. Among two forms of homonegativity, it is the old-fashioned one that expresses adherence to rigid conventional norms and values, including religious conviction about acceptable sexual and gender behaviors; it was established earlier that social conventionalism is related to a higher propensity for and acceptance of aggression in interpersonal and social relationships (Benjamin 2016;Besta et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with a three-component model of gender nonconformity prejudice (Nagoshi et al 2008), which stresses social conventionalism as the key factor of prejudice toward gender nonconformists. Among two forms of homonegativity, it is the old-fashioned one that expresses adherence to rigid conventional norms and values, including religious conviction about acceptable sexual and gender behaviors; it was established earlier that social conventionalism is related to a higher propensity for and acceptance of aggression in interpersonal and social relationships (Benjamin 2016;Besta et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…When country was used as the reference group in study 1, the interaction between independent and agentic and interdependent and communal self-construals was not statistically significantly related to identity fusion. One explanation for this finding is that one's relation with one's country might also depend on different conditions, such as political views and ideology (e.g., the link between authoritarianism and fusion with country; see Besta et al, 2015). Moreover, country was the most abstract entity I included as a reference group, and the other groups were relational.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to these principles, previous studies have shown that the state of identity fusion is strongly related to progroup behavior, as measured by charitable donations (Swann, Gómez, Huici, Morales, & Hixon, 2010) and by willingness to defend in-group members and be self-sacrificial for their good among students and adults from several countries Besta, Szulc, & Jaśkiewicz, 2015;Gómez et al, 2011a;Swann et al, 2014) and members of communities with links to militant jihad (Atran, Sheikh, & Gómez, 2014). Even ostracism increases endorsement of extreme progroup behavior for the in group among fused persons (Gómez, Morales, Hart, Vázquez, & Swann, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The identity fusion measure was a good predictor of pro-group behaviors in previous studies (e.g. Besta, Szulc, & Jaśkiewicz, 2015;Swann, Gómez, Huici, Morales, & Hixon, 2010;see Swann & Buhrmester, 2015 for overview). Thus we controlled for group adherence by including this measure.…”
Section: Methodsmentioning
confidence: 96%